(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
New method of synthesizing NH2/NH2 capped polyaniline tetramer – 4,4’-di(p-aminoanilino)-diphenylene, by oxidative condensation of 4-aminoacetanilide with N-acetyldiphenylamine and subsequent hydrolysis of the obtained 4,4’-di(p-acetylamino)-N-acetyldiphenylamine is discussed.